The latinamerican integration: dreams and realities - Arroyo, Eduardo (2009)
The article «The Latin-American integration: dreams and realities» alludes to the continental attempts for reinforce the unit between the member countries. It starts with the Americanist ideal forged during the independence and reviews the triumph of Balkanistic ideas over unionist efforts. Today America faces the USA project called ALCA (Free Trade Area of the Americas) excluding Cuba, a project left in stand by, while others have appeared like the most complete one of ALBA (Bolivarian Alliance of the Americas) including already Venezuela, Bolivia, Cuba and Nicaragua; another project is the IIRSA (Initiative for the Regional Integration of South America) and the project of the Energetic Rings headed by Chile.